Optimasi Connecting Rod Sepeda Motor Untuk Mereduksi Massa Dan Brake Specific Fuel Consumption (BSFC) - Okariawan, IDK. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
Many countries in the world at recent decade depends energy source from oil (petroleum). Oil is un-renewable energy and someday the quantity will be very low (oil crisis). Some of oil conservation needed to expand oil live, and now for Indonesia, reduce fuel consumption of automobile (particularly for motorcycle) is primary oil conservation effort. Mass reduction of automobile component is one of the way to reduce fuel consumption, from Engineering Design and Manufacture point of view so that these researches try to reduce mass of connecting rod in Motorcycle.       In this research mass reduction, that connecting rod was considering with safety design to material failure, which was quasi-static Factor of Safety (FOS). Increase of fuel efficiency effect calculated from Brake Specific Fuel Consumption (BSFC) criteria. Simulation method was a basis to find FOS and BSFC talked above.       As the result of this research, optimum connecting rod model was obtained, that has lighter mass than initial connecting rod, also enable to stand the allowable minimum FOS (4,6 for tensile load and 2,55 for compressive load). The optimum connecting rod model also enables to reduce BSFC about 6 %.